PENGARUH TOTAL ASSET TURN OVER TERHADAP RETURN ON EQUITY, RETURN ON ASSET DAN PRICE TO BOOK VALUE PADA PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2019 - Wahyu Sumarsidi; Suyatno Suyatno; Hairudinor Hairudinor (Universitas Lambung Mangkurat, 2021)
The aim of this research is to analysis the effects of total asset turnover ratio on return equity ratio, return on asset, and price to book value. This research is an explanatory-causality which tests and analysis 6 direct effects and 3 mediation effects. Target population of this research is the 25 coal mining firms that listed in Indonesian Stock Exchange at the years 2013-2019, and the sample size are 105 time series data of the 15 firms selected with purposeve sampling those can compute to observed variables include in the research model.The research findings demonstrate that the 5 positive significance direct-effect, excepted the return on equity have negative insignificance effect toward price to book value. The 3 mediations significance effect that are (1) return on equity at the effect of the total asset turnover toward return on asset, (2) return on asset at the effect of the return on equity toward price to book value, and (3) multi-phase of the return on equity and return on asset at the effect of the total asset turnover toward price to book value.Keywords: Total Asset Turnover, Return On Equity, Return On Asset, Price To Book Value, and Coal Mining Firms.